Parametric studies of DD3R particles seeding on the modified surface of α-alumina support and synthesis of DD3R zeolite membrane. Issue 15 (December 2018) - Meshkat, Aynaz; Vaezi, Mohammad Javad; Babaluo, Ali Akbar; Geranbaha, Masoud Gohar
Abstract: The effects of suspension concentration, number of coating stages and dipping time on seeding quality of DD3R particles on the ceramic supports were investigated. The supports were immersed in aqueous suspensions (0.1, 0.2 and 0.3 wt. %) of the DD3R seeds for three different dipping times 30, 90 and 240 s with different stages of 1, 2 and 3. The SEM analysis was used to study the quality of the seeded layers. The optimized seeding conditions of 0.2 wt. % suspension concentration, 2 number of coating stages and 30 s for dipping time leaded to obtain a uniform seeded layer with monolayer structure. The DD3R zeolite membrane was synthesized via hydrothermal method under the optimized seeding conditions. The XRD and SEM analyses confirmed the synthesis of DD3R membrane with proper quality. The single gas permeation results showed a good performance in the separation of CO2 from CH4 .